Embedding Sustainability Literacy with Language Teaching in Higher Education - Viqi Ardaniah; Zakiyah Dania Billah; Lastiko Endi Rahmantyo; Peter Ardhianto (JL3T (Journal of Linguistics, Literature and Language Teaching), 2025)
ABSTRACT This study contributes to the identification of sustainability literacy variables for language teaching in higher education. Prior studies have addressed sustainability literacy through curriculum development, environmental education, and technological adoption. Sustainability literacy ensures that higher education academics have sustainability knowledge, adopt and perform sustainable practices or attitudes. However, previous studies neglect how environment, economy, social variables of sustainability literacy are disseminated in language teaching. The language teaching has not addressed sustainability themes in language skill courses such as listening, speaking, reading, and writing. Thus, this study aims to generate sustainability literacy variables that can be used as sustainability themes in the language teaching. A bibliometric analysis through VOSviewer is employed to collect the variables from the Scopus database by determining keywords. The present study employs BOOLEAN search with some keywords including â€œsustainable literacyâ€, â€œsustainability literacyâ€, â€œenvironmental literacyâ€, â€œhigher educationâ€, â€œuniversityâ€, â€œinstituteâ€. In addition, inclusion criteria include journal article as type document, English language, and open access. The 106 documents met the criteria ranging from 2008 to 2024. The results indicate that there are eight groups of sustainability themes related to sustainability literacy. Of the eight groups, sustainability literacy variables selected for the language teaching consist of climate change, energy efficiency, renewable energy, economic growth, digital economy, financial knowledge, global citizenship, and knowledge sharing. The variables give implications both in practice and theory. Keywords: Sustainability literacy; higher education; language teaching; VOSviewer.